Unmanned Systems and Civil-Military Integration: Ethical and Operational Implications in Humanitarian Missions - Akbar, Muhammad Firjatullah Nur; Arif, Fadli (PT. Civil Military Center, 2026)
The rapid advancement of unmanned systems, including unmanned aerial vehicles, unmanned ground vehicles, and autonomous maritime platforms, has significantly transformed the operational landscape of humanitarian missions. These technologies enhance situational awareness, accelerate response times, and enable access to high-risk or inaccessible environments. However, their integration into humanitarian contexts introduces complex ethical, legal, and operational challenges, particularly in relation to civil-military cooperation. This study examines the role of unmanned systems in shaping contemporary humanitarian operations through a qualitative approach that combines a systematic literature review with a case study of Indonesia. The study proposes a novel conceptual framework, the Ethical-Operational Integration Model, which integrates ethical governance, operational coordination, and technological accountability. The findings indicate that while unmanned systems improve efficiency and coordination, their effective deployment depends on robust governance frameworks, ethical safeguards, and institutional alignment. This research contributes to the growing discourse on technology-enabled humanitarianism by offering an integrative perspective that bridges innovation, governance, and ethics.